PERLINDUNGAN HUKUM TERHADAP PEKERJA ATAS PENYESUAIAN UPAH PADA MASA PANDEMI COVID-19 - Evi Nur Habibah Wulandari T (Fakultas Hukum Universitas Islam Malang, 2022)
AbstractThis study aims to understand the company's authority in making adjustments to workers' wages and to find out the form of the Government's legal protection to protect workers from wage adjustments during the Covid-19 pandemic. The method used is a normative statute approach by using legal materials that refer to the norms and legislation in force. The results of this study are companies have the authority to make adjustments to workers' wages during the Covid-19 pandemic, based on agreements between employers and workers that are carried out fairly and proportionally by taking into account the survival of workers and business continuity. The Government's form of legal protection to protect workers from wage adjustments during the Covid-19 pandemic, there is a Circular Letter of the Minister of Manpower Number M/3/HK.04/III/2020 and Decree of the Minister of Manpower Number 104 of 2021 concerning Guidelines for Implementing Employment Relations During the Period The Corona Virus Disease 2019 (Covid-19) pandemic is a form of preventive legal protection. Meanwhile, the industrial relations dispute court is a form of repressive legal protection.Keywords: Covid-19 Pandemic, Wages Adjustment, WorkersAbstrakPenelitian ini bertujuan untuk memahami wewenang perusahaan dalam melakukan penyesuaian upah pekerja dan mengetahui bentuk perlindungan hukum Pemerintah untuk melindungi pekerja atas penyesuaian upah pada masa pandemi Covid-19. Metode yang digunakan adalah pendekatan yuridis normatif (statute approach) dengan menggunakan bahan-bahan hukum yang mengacu pada norma-norma serta peraturan perundang-undangan yang berlaku. Hasil dari penelitian ini adalah perusahaan memiliki wewenang untuk melakukan penyesuaian upah pekerja pada masa pandemi Covid-19, didasarkan pada kesepakatan antara pengusaha dengan pekerja yang dilakukan secara adil dan proporsional dengan memperhatikan kelangsungan hidup pekerja dan kelangsungan usaha. Bentuk perlindungan hukum Pemerintah untuk melindungi pekerja atas penyesuaian upah pada masa pandemi Covid-19, terdapat Surat Edaran Menteri Tenaga Kerja Nomor M/3/HK.04/III/2020 dan Keputusan Menteri Ketenagakerjaan Nomor 104 Tahun 2021 Tentang Pedoman Pelaksanaan Hubungan Kerja Selama Masa Pandemi Corona Virus Disease 2019 (Covid-19) sebagai bentuk perlindungan hukum preventif. Sedangkan pengadilan perselisihan hubungan industrial sebagai bentuk perlindungan hukum represif.Kata Kunci: Pandemi Covid-19, Penyesuaian Upah, Pekerja